ON CONNECTIONS BETWEEN GENERALIZED SOLUTIONS OF PDE'S OF THE FIRST ORDER - Ekaterina A. Kolpakova (Ural Mathematical Journal)
The paper is devoted to investigation of connections between generalized solutions of the Cauchy problemfor the Hamilton-Jacobi-Bellman equation and the corresponding quasilinear equation of the first order in theof case n-dimentional state space